Effect of back extensor muscle endurance training on back pain incidence rate in computer users: a pilot study - Kothapalli, Madhubabu (International Journal of Research in Medical Sciences, 2022)
Background: Sit and work for more than seven hours per day increases risk of low back pain among computer users. Prevention of low back pain emerges as an important workplace healthcare measure. The objective was to examine the effect of back extensor endurance training on back pain incidence rate and to use back endurance position hold time score as back pain predictive marker in computer users. Methods: Seventy-three subjects with low and medium back endurance position hold time score included in this randomized control trail. Subjects categorized as prevention group (n=38) and control group (n=35). Prevention group performed back endurance exercise program three times in a week for 12 weeks. Control group not received any training. Back endurance hold time score measured before and after 12 weeks for both groups with Biering-Sorensen test. Back pain incidence and severity evaluated using 100 mm visual analog scale. Results: Preventive groups’ back endurance hold time significantly high after training (p<0.05). There was inverse relationship between position hold time score and back pain incidence rate in both groups (r=-0.415 and -0.02 for both the groups). Position hold time scores from control group significantly associated with back pain incidence rate (p<0.05). Back pain incidence rate was 51.4 % (control group) and 15.7% (prevention group). Conclusions: Back extensor endurance training is effective in prevention of back pain incidence rate among high risk computer users. Future studies required to incorporates these trainings in workplace preventive health programs.